The Implementation of Distance Learning Policy in The Covid-19 Pandemic Era Through The Blended Learning Method in Pancasila and Civics - Nika Nur Aliantika; Rahmat Rahmat; Prayoga Bestari (Jurnal Civicus, 2021)
The implementation of remote policies is the answer from the Government to the problems in the world of education caused by the Covid-19 pandemic in Indonesia. The many limitations in implementing remote policies during this pandemic, cannot be separated from the problems that occur during the implementation process. Educators play an important role in the successful implementation of remotely, required to innovate and be creative in conveying learning amid all existing limitations. Therefore, this study aims to find out "The extent to which blended learning methods can help in implementing distance learning policies at SMA Labschool UPI Bumi Siliwangi". The approach in this writing uses Qualitative, with the Case Study method. The results of the study showed; 1). From the educator's point of view: a) In terms of time flexibility, the learning process can be done anywhere and anytime, b) In terms of administrative more neatly, c) In terms of administrative more neat, d) More cost-effective, e) In terms of Pancasila education and citizenship, providing a space of persuasion for educators and students. 2). Student point of view a) Able to increase the spirit of learners' learning motivation, b) Help learners better understand learning materials, c) Provide discussion space for educators and learners in PPKn subjects.